Investigating the bunkering choice determinants: The case of the port of Antwerp - Raimonds Aronietis; Christa Sys; Edwin Van Hassel; Thierry Vanelslander (Journal of Shipping and Trade (JST), 2017)
From a European, regional and local perspective, as well as from the perspective of port authorities, it is important that waterborne transport becomes sustainable. As possible solutions to comply with new types of legislation (SECA-zones), shipping companies consider amongst others the use of liquefied natural gas (LNG) and low sulphur fuel. An important aspect in the choice of fuel are the current bunker strategies of the shipping companies. Therefore, this research deals with the bunker market and wants to increase the insight into the strategy of the shipping companies, why they bunker in Antwerp or in another port (e.g. Rotterdam). Which criteria are the most important: the price per tonne, the quality of the fuel, or another characteristic (e.g. calling pattern)? The research question is answered with a discrete choice experiment, evaluating the preferences of the shipping lines. A multinomial logit model is chosen for this experiment because of the low expected number of respondents. The research is further expanded with more in-depth interviews with bunkering decision makers of various shipping companies.
Keywords: 650